MANFAAT PERNIKAHAN POLIGINI BAGI KAUM PEREMPUAN - Pawitasari, Erma (AL-TAHRIR, 2015)
Abstract: Marriage, as one of the subject domains of Islamic studies, often led to problems in a number of cases if it is related to polygamy. Polygamy was often only seen from the perspective of the needs and the existence of man. Wives who accepted polygamy were synonymous with stigma called "trouble maker wives." This point of view caused community see polygamy as a form of abuse and torture against women. However, the practice of in disguise polygamy was still going on firmly.Â  n. A male was "allowed" to have as many women as he wants, as long as it was not carried out in public registry office or religious court. Illegal polygamy had raised many social problems and made women as its victims. Studies through the perspective of the economy, particularly through the concept of supply and demand, indicated that people's attitude which opposed toward polygamy had made all women in a very poor bargaining position. The struggle of feminists to reject polygamy was a wrong step that could disadvantage womankind. That is why this study tried to explore polygamy from Islamic perspective.Â  Islam actually had given privilege to every wife to ensure the harmony of family and happiness of life. However, if a wife was not comfortable with being polygamous relationships, she could get out of his marriage without being given the burden of a child, living, as well as fearing of getting public censure. Islam gave ease to every woman to marry another better man.Ø§Ù„Ù…Ù„Ø®Øµ :Ø¥Ù† Ù…ÙˆØ¶ÙˆØ¹ "Ø§Ù„Ù†ÙƒØ§Ø" ÙƒØ£ØØ¯ Ø§Ù„Ù…ÙˆØ¶ÙˆØ¹Ø§Øª ÙÙŠ Ø§Ù„Ø¯Ø±Ø§Ø³Ø§Øª Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ©ØŒ ÙƒØ«ÙŠØ±Ø§ Ù…Ø§ Ø£Ù†Ø´Ø£Øª Ø§Ù„Ø®Ù„Ø§ÙØ§Øª ÙÙŠ Ø¬ÙˆØ§Ù†Ø¨ØŒ ÙˆÙ…Ù†Ù‡Ø§ ØªØ¹Ø¯Ø¯ Ø§Ù„Ø²ÙˆØ¬Ø§Øª. ÙˆÙ‡Ø°Ø§ Ø§Ù„ØªØ¹Ø¯Ù‘Ø¯ ÙŠÙÙ†Ø¸Ø± ÙƒØ«ÙŠØ±Ø§ Ù…Ù† Ù†Ø§ØÙŠØ© Ø§Ù„ØØ§Ø¬Ø© ÙˆÙƒÙ†Ù‡ Ø§Ù„Ø±Ø¬Ù„. ÙˆØ§Ù„Ø²ÙˆØ¬Ø© Ø§Ù„Ù‚Ø§Ø¨Ù„Ø© Ù„Ù„ØªØ¹Ø¯Ù‘Ø¯ Ù„Ù‡Ø§ Ø³Ù…Ø© "Ø§Ù„Ù…Ø±Ø£Ø© Ø°Ø§Øª Ù…Ø³Ø£Ù„Ø©". Ù‡Ø°Ù‡ Ø§Ù„ÙˆØ¬Ù‡Ø© Ù…Ù† Ø§Ù„Ù†Ø¸Ø± Ø¬Ø¹Ù„ Ø§Ù„Ù…Ø¬ØªÙ…Ø¹ ÙŠÙ†Ø¸Ø± Ø¥Ù„Ù‰ "ØªØ¹Ø¯Ø¯ Ø§Ù„Ø²ÙˆØ¬Ø§Øª" ÙƒØ´ÙƒÙ„ Ø§Ù„ØªØ¹Ø°ÙŠØ¨ Ù„Ù„Ù†Ø³Ø§Ø¡. Ù„ÙƒÙ† ÙˆÙ‚ÙˆØ¹ Ø¹Ù…Ù„ÙŠØ© Ù‡Ø°Ø§ Ø§Ù„ØªØ¹Ø¯Ù‘Ø¯ Ø®ÙÙŠØ© Ù…Ø³ØªÙ…Ø±Ù‘. ÙŠØ¬ÙˆØ² Ù„Ù„Ø±Ø¬Ù„ Ø£Ù† ÙŠÙ…Ù„Ùƒ Ù„Ù†ÙØ³Ù‡ Ø¹Ø¯Ø¯Ø§ Ù…Ù† Ø§Ù„Ù†Ø³Ø§Ø¡ Ø¹Ù„Ù‰ ØØ³Ø¨ Ø±ØºØ¨Ø§ØªÙ‡ØŒ Ø¨Ø´Ø±Ø· Ø£Ù† Ù„Ø§ ÙŠÙƒÙˆÙ† ØªØØª "Ø§Ù„Ù†ÙƒØ§Ø". Ø³Ø¨Ù‘Ø¨ Ù‡Ø°Ø§ Ø§Ù„Ù†ÙˆØ¹ Ù…Ù† Ø§Ù„ØªØ¹Ø¯Ø¯ (ØºÙŠØ± Ø§Ù„Ø±Ø³Ù…ÙŠ) Ø¥Ù„Ù‰ Ø¸Ù‡ÙˆØ± Ù…Ø´Ø§ÙƒÙ„ Ø¥Ø¬ØªÙ…Ø§Ø¹ÙŠØ© ÙˆÙˆØ¶Ø¹ Ø§Ù„Ù…Ø±Ø£Ø© Ù…Ø¸Ù„ÙˆÙ…Ø©. Ø¯Ù„Ù‘Øª Ø§Ù„Ø¯Ø±Ø§Ø³Ø© â€“ Ø¨ÙˆØ¬Ù‡Ø© Ø§Ù„Ù†Ø¸Ø± Ø§Ù„Ø¥Ù‚ØªØµØ§Ø¯ÙŠØ© â€“ ÙˆØ®Ø§ØµØ© Ø¨Ø§Ù„Ù…ÙÙ‡ÙˆÙ… " supply and demandâ€ Â " Ø£Ù† Ù…ÙˆÙ‚Ù Ø§Ù„Ù…Ø¬ØªÙ…Ø¹ Ø§Ù„Ù…Ø¹Ø§Ø±Ø¶ Ù„ØªØ¹Ø¯Ø¯ Ø§Ù„Ø²ÙˆØ¬Ø§Øª ÙˆØ¶Ø¹ Ø§Ù„Ù…Ø±Ø£Ø© ÙÙŠ Ù…ÙˆØ¶Ø¹ ØªØ³Ø§ÙˆÙ… ÙˆØ¶ÙŠØ¹. ÙˆØ¬Ù‡Ø§Ø¯ Ø§Ù„ØØ±ÙƒØ© Ø§Ù„Ù†Ø³Ø§Ø¦ÙŠØ© Ù„Ø±ÙØ¶ Ø§Ù„ØªØ¹Ø¯Ø¯ Ù‡Ùˆ Ø®Ø·ÙˆØ© Ø¶Ø§Ù„Ø© ÙˆÙ…Ø®Ø³Ù‘Ø±Ø© Ù„Ù„Ù†Ø³Ø§Ø¡ Ø£Ù†ÙØ³Ù‡Ù†Ù‘. Ù„Ø°Ø§ ÙØ¥Ù† Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© ØØ§ÙˆÙ„Øª Ø¯Ø±Ø§Ø³Ø© "ØªØ¹Ø¯Ø¯ Ø§Ù„Ø²ÙˆØ¬Ø§Øª" Ø¨Ù…Ù†Ø¸Ø§Ø± Ø§Ù„Ø¥Ø³Ù„Ø§Ù…. ÙˆÙ„Ù‚Ø¯ Ø£Ø¹Ø·Ù‰ Ø§Ù„Ø¥Ø³Ù„Ø§Ù… ØÙ‚Ø§ Ù…Ø«Ø§Ù„ÙŠØ§ Ù„Ù„Ø²ÙˆØ¬Ø© Ù„Ù„ØªØ£ÙƒØ¯ Ø¹Ù„Ù‰ Ø³Ø¹Ø§Ø¯Ø© Ø§Ù„ØÙŠØ§Ø© Ø§Ù„Ø²ÙˆØ¬ÙŠØ© ÙˆØ±ÙØ§Ù‡ÙŠØªÙ‡Ø§. Ù„ÙƒÙ† Ù„Ùˆ Ø£Ù†Ù‡Ø§ Ø´Ø¹Ø±Øª Ø¨Ø¹Ø¯Ù… Ø§Ù„Ø§Ø·Ù…Ø¦Ù†Ø§Ù† Ø¨Ø§Ù„ØªØ¹Ø¯Ù‘Ø¯ØŒ ÙŠØ¬ÙˆØ² Ù„Ù‡Ø§ Ø§Ù„Ø§Ù†ÙØµØ§Ù„ Ø¹Ù† Ø§Ù„Ù†ÙƒØ§Ø Ø¨Ø¯ÙˆÙ† Ø¹Ø¨Ø¡ Ø§Ù„Ø£ÙˆÙ„Ø§Ø¯ØŒ ÙˆØ§Ù„Ù†ÙÙ‚Ø§ØªØŒ Ø£Ùˆ Ø§Ù„Ø®ÙˆÙ Ù…Ù† Ù„ÙˆÙ…Ø© Ø§Ù„Ù…Ø¬ØªÙ…Ø¹. ÙˆØ£Ø¬Ø§Ø² Ø§Ù„Ø¥Ø³Ù„Ø§Ù… Ø£Ù† ØªÙ†ÙƒØ Ù‡ÙŠ Ù…Ù† Ø±Ø¬Ù„ Ø¢Ø®Ø± Ø£ØØ³Ù† Ù…Ù† Ø²ÙˆØ¬Ù‡ Ø§Ù„Ø£ÙˆÙ„.Abstrak: Pernikahan, sebagai salah satu dari ranah subyek kajian Islam, seringkali memunculkan permasalahan dalam sejumlah hal, termasuk ketika ia direlasikan dengan poligami. Poligami seringkali hanya dilihat dari perspektif kebutuhan dan eksistensi laki-laki. Istri yang menerima poligami identik dengan stigma â€œistri bermasalah.â€ Sudut pandang ini menyebabkan masyarakat memandang poligami sebagai bentuk penyiksaan terhadap perempuan. Namun praktik poligami secara terselubung tetap terjadi. Laki-laki â€œdiperbolehkanâ€ memiliki perempuan sebanyak yang ia mau, selama tidak dilakukan di dalam lembaga pernikahan. Poligami ilegal menimbulkan berbagai persoalan sosial dan menempatkan perempuan sebagai korban. Kajian melalui perspektif ekonomi, khususnya melalui konsep supply and demand, menunjukkan bahwa sikap masyarakat yang antipoligami telah menempatkan seluruh wanita dalam posisi tawar yang sangat rendah. Perjuangan kaum feminis untuk menolak poligami merupakan langkah yang tersesat dan justru merugikan kaum perempuan. Karenananya kajian ini mencoba untuk mengeksplorasi poligami melalui perspektif Islam. Islam sejatinya memberi hak istimewa kepada istri untuk memastikan keharmonisan rumah tangga dan kebahagiaan hidup. Namun, bila istri tidak nyaman dengan poligami, ia boleh keluar dari pernikahannya tanpa beban anak, nafkah, maupun kekhawatiran mendapatkan celaan masyarakat. Islam memberi kemudahan untuk menikah dengan laki-laki lain yang lebih baik.Keywords: poligami, supply, demand, perempuan, istri, perspektif Islam.